Classification of Involuntary Movements in Dogs: Myoclonus and Myotonia. (30th May 2017) - Lowrie, M.; Garosi, L.
Abstract : Myoclonus is a sudden brief, involuntary muscle jerk. Of all the movement disorders, myoclonus is the most difficult to encapsulate into any simple framework. On the one hand, a classification system is required that is clinically useful to aid in guiding diagnosis and treatment. On the other hand, there is need for a system that organizes current knowledge regarding biological mechanisms to guide scientific research. These 2 needs are distinct, making it challenging to develop a robust classification system suitable for all purposes. We attempt to classify myoclonus as "epileptic" and "nonepileptic" based on its association with epileptic seizures. Myotonia in people may be divided into 2 clinically and molecularly defined forms: (1) nondystrophic myotonias and (2) myotonic dystrophies. The former are a group of skeletal muscle channelopathies characterized by delayed skeletal muscle relaxation. Many distinct clinical phenotypes are recognized in people, the majority relating to mutations in skeletal muscle voltage‐gated chloride ( CLCN1 ) and sodium channel ( SCN4A ) genes. In dogs, myotonia is associated with mutations in CLCN1 . The myotonic dystrophies are considered a multisystem clinical syndrome in people encompassing 2 clinically and molecularly defined forms designated myotonic dystrophy types 1 and 2. No mutation has been linked to veterinary muscular dystrophies. We detail veterinary examples of myotonia and attempt classification according to guidelines used in humans. This more precise categorization of myoclonus and myotonia aims to promote the search for molecular markers contributing to the phenotypic spectrum of disease. Our work aimed to assist recognition for these 2 enigmatic conditions.